EVALUATING THE EFFECT OF THE FLUCTUATIONS ON THE ACTUAL EXCHANGE RATE ON THE DIRECT FOREIGN INVESTMENT IN UGANDA - Salam Anwar Ahmed; Harith Adnan Mohammad; Asmaa Taha Mukhlaf (Scholar Express Journals, 2022)
This paper studied the effect of the changes in the exchange rates on direct foreign investment flow in Uganda during the period 1981-2018 by using ARDL model. The study found that the changes in the actual exchange rate had a negative effect on the foreign investment flow in the short term and a positive effect on the foreign investment flow in the long term. The most important recommendations the study reached was the necessity for Uganda to keep the flexibility of the exchange rate to guarantee its stability in the long term and positively reflects on the direct foreign investment flow to the country.
Keywords: found; changes; actual; exchange